Analysis of Water Resources Carrying Capacity in the Greater Bay Area Based on Index Probability Distribution - CHEN Juan; WANG Sen (Renmin Zhujiang)
The Greater Bay Area is the forefront of China’s reform and opening up and the important engine of economic growth.Water resources have become a key factor driving or restricting the sustainable economic development of the Greater Bay Area.Taking the Greater Bay Area as the research object,this paper constructs a three-level index system of water resources carrying capacity based on two subsystems of water resources environment and economic society.It also proposes an analysis model of water resources carrying capacity based on index probability distribution.The comprehensive evaluation of water resources carrying capacity in nine cities of the Greater Bay Area is carried out by combining the coupling coordination degree and the index probability distribution,which are mutually verified.The results show that the comprehensive value of water resources carrying capacity in Greater Bay Area mostly in grade III. Foshan is slightly higher than grade III and located in grade IV.The water resources carrying capacity of Zhuhai is relatively better,while that of Foshan is relatively poor.Regarding the coordination degree of water resources environment and economic society,Foshan exhibits moderate imbalance,while other cities all have low coordination.In view of this,some suggestions are provided,including controlling the total amount of water use,rationally allocating water resources,optimizing and adjusting the industrial structure,improving water use efficiency,protecting the water environment,and strengthening water conservation.